The Effect of Soybean Milk (Glycine Max L.) on Reducing Blood Pressure and Cholesterol Levels in Women of Reproductive Age - Simbolon, Agustina; Sumarni , Sri; Anwar, Choiroel (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: Women of reproductive age often experience problems with blood pressure and cholesterol levels. Therefore, researchers innovated in an effort to stabilize blood pressure and cholesterol levels in women of reproductive age by providing an intervention of soy milk. The purpose of this study was to determine the effect of soy milk administration on reducing blood pressure and cholesterol levels in women of reproductive age. Subjects and Methods: This study used a Quasi-Experimental design with Pretest-Posttest Control. The research location was the Pangaribuan Community Health Center, Pangaribuan District, North Tapanuli Regency. Data collection was conducted in June 2025. The two groups consisted of an intervention group receiving 40 grams of soy milk and a control group receiving education on blood pressure and cholesterol levels. The dependent variables studied were blood pressure and cholesterol levels, and the independent variable was soy milk. The analysis techniques used were Repeated Measures ANOVA and Paired Sample T-Test. Results: The average systolic blood pressure in the intervention group after being given soy milk was lower (Mean= 133.92; SD= 10.20) compared to before the intervention (Mean= 143.82; SD= 5.48) and was statistically significant (p <0.001), the average diastolic blood pressure in the intervention group after being given soy milk was lower (Mean= 86.88; SD= 5.08) compared to before the intervention (Mean= 92.88; SD= 5.44) and was statistically significant (p <0.001), the average cholesterol level in the intervention group after being given soy milk was lower (Mean= 232.94; SD= 7.56) compared to before the intervention (Mean= 261.24; SD= 13.27) and was statistically significant (p <0.001). Conclusion: Soy milk is effective in lowering systolic and diastolic blood pressure and cholesterol levels in women of childbearing age.